Long term survival of a biliary atresia patient by repeated liver transplantations for portopulmonary hypertension in addition to the hepatopulmonary syndrome - Shintaro Hayashida; Yukihiro Inomata; Yuki Ohya; Toshiyuki Matsumura (Elsevier, 2023)
A female patient after Kasai procedure for biliary atresia had a hepatopulmonary syndrome(HPS), and underwent living donor liver transplantation (LDLT)at 15 years old. HPS improved once, but unfortunately recurred with the graft dysfunction 10 years later, and portopulmonary hypertension (PoPH) additionally complicated at 29 years old. Following the treatment with epoprostenol, she was saved by the deceased donor liver transplantation (DDLT) at 33 years old. After the retransplant, both the HPS and PoPH quickly improved, and she has been doing well as the part time worker. Coexist of both the long-term pulmonary complications due to the liver dysfunction is quite rare, and this case documented the reversibility of the both by liver transplantation. The entire course also taught us that the patience and intimate cooperation with the patient were essential in such a long-lasting transitional care of the biliary atresia throughout the pediatric and the adolescence.